The slope is given by rise over run, or difference in y over difference in x. Therefore in this problem that is (-2-4)/(-3-3) => (-6)/(-6) => 1
Final answer:
The slope is 1.
Hope I could help :)
Answer:
D = 0; one real root
Step-by-step explanation:
Discriminant Formula:
![\displaystyle \large{D = {b}^{2} - 4ac}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Clarge%7BD%20%3D%20%20%7Bb%7D%5E%7B2%7D%20%20-%204ac%7D)
First, arrange the expression or equation in ax^2+bx+c = 0.
![\displaystyle \large{ {x}^{2} + 6x = - 9}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Clarge%7B%20%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%3D%20%20-%209%7D)
Add both sides by 9.
![\displaystyle \large{ {x}^{2} + 6x + 9 = - 9 + 9} \\ \displaystyle \large{ {x}^{2} + 6x + 9 = 0}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Clarge%7B%20%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%2B%209%20%3D%20%20-%209%20%2B%209%7D%20%5C%5C%20%20%5Cdisplaystyle%20%5Clarge%7B%20%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%2B%209%20%3D%20%200%7D)
Compare the coefficients so we can substitute in the formula.
![\displaystyle \large{a {x}^{2} + bx + c = {x}^{2} + 6x + 9 }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Clarge%7Ba%20%7Bx%7D%5E%7B2%7D%20%20%2B%20bx%20%2B%20c%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%2B%209%20%7D)
Substitute a = 1, b = 6 and c = 9 in the formula.
![\displaystyle \large{D = {6}^{2} - 4(1)(9)} \\ \displaystyle \large{D = 36 - 36} \\ \displaystyle \large{D = 0}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Clarge%7BD%20%3D%20%20%7B6%7D%5E%7B2%7D%20%20-%204%281%29%289%29%7D%20%5C%5C%20%20%5Cdisplaystyle%20%5Clarge%7BD%20%3D%20%2036%20-%2036%7D%20%5C%5C%20%20%5Cdisplaystyle%20%5Clarge%7BD%20%3D%20%200%7D)
Since D = 0, the type of solution is one real root.
We know that the sum of the inner angles of any triangle is 180º
72º + (7x + 3)º + (3x + 5)º = 180º
72º + 7xº + 3º + 3xº + 5º = 180
7xº + 3xº = 180º - 72º - 3º - 5º
10xº = 100º
![x^0 = \frac{100^0}{10^0}](https://tex.z-dn.net/?f=x%5E0%20%3D%20%20%5Cfrac%7B100%5E0%7D%7B10%5E0%7D%20)
![x^0 = 10\to\:\boxed{\boxed{x = 10^0}}\end{array}}\qquad\quad\checkmark](https://tex.z-dn.net/?f=x%5E0%20%3D%2010%5Cto%5C%3A%5Cboxed%7B%5Cboxed%7Bx%20%3D%2010%5E0%7D%7D%5Cend%7Barray%7D%7D%5Cqquad%5Cquad%5Ccheckmark)
The sum of the external angle (9y + 1)º with inner angle (3x + 5) = 180 °, <span>Replace the measure of "x" found:
</span>
(9y + 1)º + (3x + 5)º = 180º
9yº + 1º + 3xº + 5º = 180º
9yº + 1º + 3.(10)º + 5º = 180º
9yº + 1º + 30º + 5º = 180º
9yº = 180º - 1º - 30º - 5º
9yº = 144º
![y^0 = \frac{144^0}{9^0}](https://tex.z-dn.net/?f=y%5E0%20%3D%20%20%5Cfrac%7B144%5E0%7D%7B9%5E0%7D%20)
![y^0 = 16\to\:\boxed{\boxed{y = 16^0}}\end{array}}\qquad\quad\checkmark](https://tex.z-dn.net/?f=y%5E0%20%3D%2016%5Cto%5C%3A%5Cboxed%7B%5Cboxed%7By%20%3D%2016%5E0%7D%7D%5Cend%7Barray%7D%7D%5Cqquad%5Cquad%5Ccheckmark)
Answer:
<span>
The measures of "x" and "y" are respectively: 10º and 16º</span>
Step-by-step explanation:
wow, how complicated can one phrase this ...
the point being :
1 ft = 12 in and vice versa (1 in = 1/12 ft)
so, any measurements given in feet but needed in inches need to be multiplied by 12.
and any measurements given in inches but needed in feet need to be divided by 12.
so,
3.5 ft = 3.5×12 = 7/2 × 12 = 7×6 = 42 in
27 in = 27/12 = 9/4 = 2 1/4 or 2.25 ft